The book of Dead Days - Sedgwick, Marcus (New York : Wendy Lamb Books, 2004)
With the help of his servant and an orphan girl, a magician named Valerian searches graveyards, churches, and underground waterways for a book he hopes will save him from a pact he has made with evil.
"End of Book One"--P. [275].
Keywords: Magicians -- Fiction; Magic -- Fiction; Orphans -- Fiction; Lost and found possessions -- Fiction; Horror stories